Nucleolipids of the Cancerostatic 5‐Fluorouridine: Synthesis, Adherence to Oligonucleotides, and Incorporation in Artificial Lipid Bilayers. Issue 2 (February 2014) - Malecki, Edith; Ottenhaus, Vanessa; Werz, Emma; Knies, Christine; Montilla Martinez, Malayko; Rosemeyer, Helmut
Abstract 5‐Fluorouridine (1a) was converted to its N(3)‐farnesylated nucleoterpene derivative 8 by direct alkylation with farnesyl bromide (4). Reaction of the cancerostatic 1a with either acetone, heptan‐4‐one, nonadecan‐10‐one, or hentriacontan‐16‐one afforded the 2′, 3′‐O‐ketals 2a–2d. Compound 2b was then first farnesylated (→5) and subsequently phosphitylated to give the phosphoramidite 6. The ketal 2c was directly 5′‐phosphitylated without farnesylation of the base to give the phosphoramidite 7. Moreover, the recently prepared cyclic 2′, 3′‐O‐ketal 11 was 5′‐phosphitylated to yield the phosphoramidite 12. The 2′, 3′‐O‐isopropylidene derivative 2a proved to be too labile to be converted to a phosphoramidite. All novel derivatives of 1a were unequivocally characterized by NMR and UV spectroscopy and ESI mass spectrometry, as well as by elemental analyses. The lipophilicity of the phosphoramidite precursors were characterized by both their retention times in RP‐18 HPLC and by calculated log P values. The phosphoramidites 6, 7, and 12 were exemplarily used for the preparation of four terminally lipophilized oligodeoxynucleotides carrying a cyanine‐3 or a cyanine‐5 residue at the 5′‐(n–1) position (i.e., 14–17). Their incorporation in an artificial lipid bilayer was studied by single‐molecule fluorescence spectroscopy and fluorescence microscopy.